Universal health coverage and public-private arrangements within Sri Lanka's mixed health system: Perspectives from women seeking healthcare. (March 2022) - Kumar, Ramya; Birn, Anne-Emanuelle; Bhuyan, Rupaleem; Wong, Josephine Pui-Hing
Abstract: Universal health coverage (UHC), a target of the United Nations' third Sustainable Development Goal on health, refers to people having access to essential healthcare services without suffering financial hardship. The World Bank and other leading global health actors champion mixed health systems—in which government and privately-financed market delivery coexist—as a sustainable model for UHC. Yet, little is known about what these public-private arrangements mean for women, a crucial partaker of UHC in low- and middle-income countries (LMICs). Using a critical feminist approach, this study explores how women negotiate access to public and private healthcare services within Sri Lanka's state-dominant mixed health system. Data were generated through focus group discussions and interviews with women residents of an urban division in Kandy, a city seeing rapid private healthcare expansion in central Sri Lanka. Notwithstanding policies of universality guiding public sector delivery, out-of-pocket payments burden socially and economically disadvantaged women. They use private services to fill gaps in the public system, and consult dual practitioners privately, to pave way for better (public) care. By contrast, wealthier women opt for private outpatient care, but capitalize on the dual practitioners to obtain priority access to oversubscribed services at public hospitals. Most women, regardless of social location, combine public with private, albeit to varying degrees, to save on household expenses. Relying on women's invisible care work, these public-private "hybrid" routes of access within Sri Lanka's poorly regulated mixed health system, reinforce social inequalities and individualize the responsibility for healthcare. The article throws light on the messiness of access within mixed systems and demands closer scrutiny of calls for private sector engagement in the quest for UHC in LMICs. Highlights: Public-private arrangements reinforce inequality and individualize the onus for healthcare. Mixed systems that rely on out-of-pocket payments dispossess people accessing care. Hybrid routes of access expand "choices" for affluent women and their families. Mixed systems create opportunities for profitmaking for physicians and the industry. Public-private arrangements demand invisible care work, usually undertaken by women.